Influence of Soybean Meal on Intestinal Mucosa Metabolome and Effects of Adenosine Monophosphate-Activated Protein Kinase Signaling Pathway in Mirror Carp (Cyprinus carpio Songpu) - Zhao, Jingyi; Xu, Qiyou (Frontiers in Marine Science, 2022)
This study aimed to explore the influence of soybean meal on intestinal mucosa metabolome and signaling pathway of mirror carp (Cyprinus carpio Songpu) by integrating liquid chromatography-tandem mass spectrometry (LC-MS/MS)-based metabolomics. Fish meal (Con) was control group, soybean meal (Dou) group, AMPK activator (300 mg kg–1 Metformin, Met) and AMPK inhibitor (0.2 mg kg–1 Compound-c, c-Com) which added to soybean meal were experimental groups. The metabolome profiles of the intestinal mucosa were determined in fish fed diets Con, Dou, Met, and c-Com on 7th and 59th day. The results were shown: compared with the Con group, the weight gain rate and the specific growth rate of fish experimental groups were significantly decreased (P < 0.05), feed conversion ratio (FCR) was significantly increased (P < 0.05). Compared with the Con group, sphingosine, glycocholic acid, majorities of sugar metabolites were up-regulated, and phosphatidylcholine (PC) and lysophosphatidylcholine (LysoPC), amino acids were reduced significantly in all experiment groups (P < 0.05). Oxidized glutathione was up-regulated in Dou on 7th day, Met on 7th and 59th day (P < 0.05). ADP (adenosine diphosphate) and AMP (adenosine monophpsphate) were up-regulated in Dou, Met, c-Com on 59th day (P < 0.05). Compared with the Dou group, sphingosine was down-regulated on 7th day, up-regulated on 59th day in Met and on 7th and 59th day in c-Com (P < 0.05). Oxidized glutathione and isocitrate on 7th day, L-Valine, L-histidine, and L-isoleucine on 59th day were up-regulated in Met (P < 0.05). Nucleoside metabolites and ADP were up-regulated in c-Com on 7th day (P < 0.05). In conclusion, soybean meal influenced intestinal mucosa metabolic processes, including lipid, amino acid, sugar, apoptosis, and oxidative injury; and changed energy metabolism in intestinal mucosa, enriched in the AMPK, TOR, FoxO signaling pathway; Metformin could aggravate oxidative damage, alleciated apoptosis for the short term, and aggravate apoptosis, improve carbohydrate catabolism and amino acid anabolism for the long term; Compound-c exacerbated apoptosis. repaired oxidative damage, and enhanced nucleoside catabolism.